Indonesian Islamic Populism and Global Framing: A Content Analysis of the 212 Demonstration by the Greatpowers’ News Agencies - Muhammad Qobidl 'Ainul Arif; Evi Murti Wardhani (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2022)
Brexit phenomenon and Donald Trump’s victory in the U.S. presidential election in 2016 simultaneously sent a signal of the populism movement spreading throughout the world. In Indonesia indeed, Jakarta gubernatorial election stimulated the heat of Indonesian political atmosphere after the Qur'an blasphemy scandal of the incumbent Governor ‘Ahok’ that eventually triggered the biggest demonstration in Indonesian Islamic history namely the 212 Demonstration. This research aims to describe the news coverage of the 212 Demonstration from news agencies belong to the Greatpowers, such as VOA, Sputnik, Xinhua, Deutsche Welle, and BBC by using the documentation method and content analysis. This research found that the Greatpowers’ news agencies framed the 212 Demonstration as an extraordinary event and political strategy of anti-government politicians to gain a short-term benefit. Surprisingly, there was not any Greatpower's media that framed the Islamic populism event of the 212 Demonstration as purely religious movement.